The haunting of medical journals: how ghostwriting sold "HRT". - Adriane J Fugh-Berman (Public Library of Science (PLoS), 2010)
Adriane Fugh-Berman examines documents unsealed in recent litigation to investigate how pharmaceutical companies promoted hormone therapy drugs, including the use of medical writing companies to produce ghostwritten manuscripts and place them into medical journals.